Germany : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper on Germany reviews investment trends and business capital stock in Organization for Economic Co-operation and Developmenta(OECD) countries. Sharp wage increases are found to boost capital formation in the short term as employers substitute capital for labor at a rate that adjusts to the higher relative price for labor. To limit the political economy biases to fiscal policy, the paper explores options to strengthen budgetary institutions, notably more transparency; stronger budgetary rules; and more room for Lander governments to mobilize revenue and tailor spending to local circumstances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet